INSURING THE NATION’S DESTINY: REDUCING THE DIGITAL DIVIDE - Booth, William (Online Learning, 2006)
“Closing the digital divide is a national challenge among historically black colleges and universities (HBCUs),” writes White examining the state of information technology readiness of five four-year HBCUs in the Commonwealth of Virginia. The inequalities created by the digital divide have the potential of undermining the effort of HBCUs in educating an “African American workforce capable of fully participating in a global information economy”. The National Association for Equal Opportunity in Higher Education (NAFEO), a nonprofit Black college association representing the interests of HBCUs in its HBCU Technology Assessment Study (TAS) produced the most comprehensive report of its kind in assessing the computing resources, networking, and connectivity of the Historic Black Colleges and University serves as the primary source for this narrative.